An essay upon business cycle facts: The Turkish case - (:unkn) unknown (My University, 2006)
In our paper, we try to investigate the main determinants of Turkish business cycles. Having examined some important issues of interest in business cycle theory, we estimate the business cycle stylized facts for the Turkish economy and compare the estimation results obtained in this paper to some benchmark papers chosen in business cycle literature. All in all, our estimation results give support to the importance of supply side models in explaining Turkish business cycles in line with contemporaneous Real Business Cycle Theory.

Çalısmamızda, Türk iç çevrimlerinin baslıca belirleyicileri arastırılmaya çalısılmaktadır. Đs çevrim kuramlarının önemli bulunan bazı özellikleri açıklandıktan sonra Türkiye ekonomisi üzerine bir deneme gerçeklestirilmis ve elde edilen tahmin sonuçları iktisat yazınında is çevrim kuramlarının olusumunu ortaya koyan baslıca çalısmalarda elde edilen tahmin sonuçları ile karsılastırılmıstır. Sonuç olarak, tahmin bulgularımız çağdas reel is çevrim kuramını destekler nitelikte sonuçlar üretmis, Türk iç çevrimlerini açıklamaya yönelik arzyönlü olusturulacak kuramsal ve uygulama içerikli çalısmaların önemi vurgulanmıstır.
Türk is çevrimleri üzerine bir deneme